The Effect of Supervision and Work Culture on Employee Work Productivity at UPT. Rawa Indah Market Bontang - Agus, Ihwan; Putri, Elmalia; Sari, Delvi Indah Ratna (Universitas Muhammadiyah Palu, 2025)
The purpose of this research is to determine the influence of supervision and work culture on employee work productivity at UPT. Rawa Indah Market Bontang. This research method is descriptive-quantitative, using data collection techniques such as observation, documentation, questionnaires and interviews. The population in this study were employees of the UPT. Rawa Indah Market Bontang with a sample size of 44 respondents. The analysis technique used is multiple linear regression with the SPSS version 16 application. The results of the research show that from the results of the partial test or T test on supervision, results are tcount 4.441 > ttable 2.018 and work culture are tcount 11.690 > ttable 2.018 with a significance of 0.00 < 0.05. The results of the simultaneous test or Ftest in this study obtained Fcount of 150.406 > Ftable 3.23 with a significance of 0.00 < 0.05. From the results of the T Test and F Test, it is known that the supervision and work culture on employee work productivity at UPT. Rawa Indah Market Bontang